HUBUNGAN KAUSALITAS ANTARA KREDIT PERBANKAN DAN TINGKAT PRODUKTIVITAS DI KALIMANTAN BARAT - B01111057, DJULIANUS (Jurnal Curvanomic, 2016)
This research titled is "Causality Relationship Between Bank Credit and Productivity Level In West Kalimantan". The aim of this study was to obtain and analyze empirical evidence about the causality relationship between bank credit disbursed and productivity level in West Kalimantan. This study was conducted by using Granger causality test that was processed using Eviews 6.0 as tools of analysis. This research use secondary data that are bank credit and productivity data in West Kalimantan from 2005-2014 (time series) with a quarter of the data so that the amount of data observation are 40 data.The results showed a two-way causality relationship between variable of bank credit and variable of productivity level in West Kalimantan. Level of significant trust of two variables is on 5% and the probability value is smaller than the level of significant trust on 5%, so that bank credit (X) significantly affect the level of productivity (Y) and conversely the level of productivity (Y) significantly affect bank credit in West Kalimantan.Keywords: Causality, Bank Credit and Productivity Level.